The preparation of UV-cured superhydrophobic cotton fabric surfaces by electrospinning method - KARTAL, İLYAS; ÇAKIR, MUSTAFA; YILDIZ, ZEHRA (SAGE PUBLICATIONS LTD, 2014)
Electrospinning was used for the coating of the polyurethane/silica hybrid solutions on the cotton fabric surface. An ultraviolet curing process was performed on the collector by an ultraviolet lamp positioned inside the electrospinning cabin. In order to investigate the effect of fluorinated, silane-functionalized urethane (inorganic part) content on the water-repellency; five different fluorinated concentrations (10%, 20%, 30%, 40%, and 50% by weight) were used. The disappearance of isocyanate peaks during the silane-functionalized urethane synthesis was observed by Fourier transform infrared spectroscopy. Surface morphology and elemental analysis of the coated cotton fabric surfaces was investigated by scanning electron microscopy and energy dispersive spectroscopy analysis respectively. Water-repellency was evaluated by contact angle measurements. A sample that contained 50% inorganic part showed a contact angle of 154.5 degrees. Samples were thermally characterized by differential scanning calorimetry. Glass transition temperature of the synthesized hybrid polymer increased with increasing inorganic part ratio. Additionally, abrasion resistance and crease recovery angle tests were performed to evaluate the effect of fluorinated part percentage on the mechanical and comfort properties of fabrics.
Keywords: PU; silica hybrids; sol-gel; electrospinning; water-repellency; UV curing; WATER-REPELLENT PROPERTIES; ANGLE